The legal critiques of the Computer Crimes Act 1997 in regulating cybercrime / Associate Professor Dr Zaiton Hamin, Hartini Saripan and Rafizah Abu Hassan - Hamin, Zaiton; Saripan, Hartini; Abu Hassan, Rafizah (Research Management Institute (RMI), 2011)
From the practical legal perspective and engaging at the instrumental and normative levels, this research attempts to focus on the legal critiques of the Computer Crimes Act 1997. In particular, on the question of what is cybercrime, why is reform needed to the substantive provisions of the said Act and what changes are sought for as well as the rationales in reforming the said Act. Issues affecting the degree or kind or both that drive the need for reform of the 1997 Act will be also be discussed. In line with the approach of common law jurisdictions, in particular the United Kingdom and Singapore as well as the Cybercrime Convention 2001, the research will examine the problems of substantive law, specifically the provisions that may be inadequate to cover certain cybercrimes such as distributed denial of service and the provisions that may in fact cover too wide an area of conduct. Also, from the theoretical level, philosophical issues involved in cybercrime, in particular the problem of identifying legal interests and emerging legal interests will be examined.